Synthesis, characterization and antimicrobial activity of copper (II) complexes of some hydroxybenzaldimines and their derivatives - Sobola, Abdullahi Owolabi (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
This study focuses on the antimicrobial activity of Cu(II) complexes of some orthohydroxybenzaldimines and its derivatives. Four different categories of Schiff base ligands were prepared by condensing salicylaldehyde, o-vanillin, p-vanillin and vanillin with p- and osubstituted anilines; 1-aminonaphthalene; 2- and 3-aminopyridine; 2- and 3- aminomethylpyridine as well as 2-aminobenzimidazole. The last category was prepared from ophenylenediamine and o-vanillin. The Schiff base ligands have been characterized by a combination of elemental analysis and spectral (Â¹H- and Â¹Â³C-NMR, UV/Visible, infrared and Raman) data. The existence of strong intramolecular hydrogen bonding in the orthohydoxybenzaldimines was evident from the chemical shift values of the hydroxyl proton in the Â¹H-NMR spectra of the Schiff base ligands. The hydroxyl proton resonates at high frequency and thus absorbed far downfield at 13.46-11.83 ppm, reflecting the presence of hydrogen bonding between the hydroxyl proton and the imine nitrogen. In the p-substituted aniline analogues of the Schiff base, a plot of the chemical shift values of the hydroxyl proton against the Hammett's substituent parameters gave a linear correlation between the electronegativities of the substituents and the chemical shift values. The nitro group with the highest electronegativity caused the least deshielding of the hydroxyl proton and thus absorbed upfield compared to the less electronegative substituents such as the CH3 and OCH3 analogues. Likewise, in the solid state infrared spectra of the ligands, the hydroxyl stretching band of the ortho-hydroxyl Schiff base ligands was observed as a very broad band and at much lower frequency, 3100-2100 cmâ »Â¹, indicating the existence of strong intramolecular hydrogen bonding. In the same vein, Â¹H- and Â¹Â³C-NMR spectral data for the Schiff base ligands indicated that the prepared compounds exist in the enol form in aprotic solvent, chloroform. The methine proton appeared as singlet and there was no carbonyl signal in the Â¹Â³C-NMR spectra of the Schiff base ligands. This was supported by the infrared data having no vibrational band attributable to the carbonyl stretching of the keto-form of the Schiff base ligands in solid state. However, the UV/Visible study of the Schiff base ligands in protic solvent, methanol, suggested the existence of some of the Schiff base ligands in keto-enol form. A band at greater than 400 nm was observed in the UV/Visible spectra of the ligands and this has been attributed to the presence of the keto form of orthohydroxyl Schiff base ligands in solution. A plot of the molar absorptivity (Îµ) of the band at greater than 400 nm against Hammett substituent parameters revealed that the intensity of the bands increased with the electronegativity of the substituents. The Cu(II) complexes of salicylaldehyde, o-vanillin and a few p-vanillin based Schiff base ligands are reported in this work. It was observed that introduction of Cu(II) ions into the ligand system resulted in the hydrolysis of the imine band in few cases. All the isolated complexes have been characterized by elemental analysis, conductivity measurement, infrared and UV/Visible spectral data. The structures of three of the Cu(II) complexes were further confirmed by X-ray single crystal diffraction. The Schiff base ligands either coordinated as neutral base through the imine nitrogen or via the imine nitrogen and the phenolic oxygen atoms. In addition, the benzimidazole-based and ovan-2-pico analogues equally coordinated through the imidazole N-3 nitrogen and the azine nitrogen respectively; thus acted as tridentate. In general, the synthesized Cu(II) complexes fell into seven categories viz: [Cu(LH)Cl(Hâ‚‚O)]Cl; [Cu(LH)â‚‚Clâ‚‚].xHâ‚‚O; [CuLâ‚‚]; [Cuâ‚‚Lâ‚‚]; [Cu(LH)Cl(Hâ‚‚O)]Cl; and [MLCl]. The Cu(II) complexes of the form, M(LH)â‚‚Clâ‚‚.xHâ‚‚O were either 1:1 or non-electrolyte in methanol and DMF. The third category, CuLâ‚‚, was however, non-electrolyte existing as neutral four coordinate Cu(II) complexes. X-ray single crystal structure of Cu(II) complexes derived from the ammonia-based Schiff bases revealed a square planar geometry for the complexes and this agreed with the planar geometry that has been reported for Cu(II) complexes of N-arylsalicylaldimines of the type studied in this work. The complexes, [Cuâ‚‚Lâ‚‚], resulted from the ortho-hydroxyaniline analogues and were polymeric with the Schiff base ligands coordinating to the Cu(II) ions as tridentate dibasic via the imine nitrogen, phenolic oxygen and the aminophenolic oxygen atoms. Cu(II) complexes prepared from ovan-2-ampy and ovan-2-pico Schiff bases were of the forms [Cu(LH)Cl(Hâ‚‚O)]Cl and [CuLCl] respectively. The X-ray crystal structure of [Cu(ovan-2- pico)Cl] revealed a four-coordinate square planar geometry for the complex. In the same vein, the o-phenylenediamine complexes were of the form [Cu(L)(Hâ‚‚O)], with the X-ray crystal structure of [Cu(bis-ovanphen)(Hâ‚‚O)] revealing a square pyramidal geometry. The Schiff base ligands and the isolated Cu(II) complexes have been evaluated for their antimicrobial activity against three bacterial strains (Escherichia coli ATCCÂ® 8739â„¢*, Staphylococcus aureus subsp. aureus ATCCÂ® 6538â„¢* and Bacillus subtilis subsp. spizizeni ATCCÂ® 6633â„¢*) and one fungal strain, Candida albicans ATCCÂ® 2091â„¢*, using agar disc diffusion and broth dilution techniques. It was observed that the presence of the methoxyl group at the ortho-position of the aldehyde moiety of the Schiff base ligands enhanced the activity of the ligand tremendously and thus the o-vanillin analogues showed the highest potency against the tested organisms. In addition, the hydroxyaniline analogues were equally the most promising of all the substituted aniline based Schiff bases. The o-vanillin analogues of the aminopyridines and aminomethylpyridines also exhibited significant activity against the tested organisms. All the 2-aminobenzimidazole series were active against the tested organisms. It should be noted that E. coli was the least susceptible of all the microorganisms while the highest potency was exhibited against the fungus of choice, Candida albicans. Lastly, chelation of the Schiff base ligands with Cu(II) ions did not have significant influence on the activity of the free ligands.
Keywords: Copper; Schiff bases; Ligands